Pembuatan Prosedur Tunjuk Silang Arsip Kartografi dan Kearsitekturan pada Upa Kearsipan Politeknik Negeri Malang - Abrari Thoriq Rizky; Diana Eka Poernamawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to develop a cross-reference procedure for cartographic and architectural archives at the Archival Service Unit (UPA Kearsipan) of Politeknik Negeri Malang (POLINEMA) to improve the efficiency of archival retrieval, which has previously been suboptimal. The research employed Action Research using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages, with archivists actively involved as research subjects. Data were collected through in-depth interviews, limited participant observation, and the System Usability Scale (SUS) questionnaire. Qualitative data were analyzed descriptively, while quantitative data from the SUS were processed to obtain usability scores. The resulting procedure includes identifying needs, gathering key information, preparing and completing cross-reference cards, assigning identification numbers, creating metadata, and placing the cards. Implementation results indicated a significant improvement in archive retrieval, with an average SUS score of 76.6, classified as “good” in usability and “high” in acceptability. The procedure proved relevant, practical, and aligned with the operational needs of UPA Kearsipan POLINEMA. The study recommends continuous implementation, regular evaluation, and integration with digital systems, while suggesting future research to adapt the procedure for other archive types and explore technology-based cross-referencing for digital archives.